Dual‐Carbon Enhanced FeP Nanorods Vertically Grown on Carbon Nanotubes with Pseudocapacitance‐Boosted Electrochemical Kinetics for Superior Lithium Storage. (7th February 2019) - Hou, Bao‐Hua; Wang, Ying‐Ying; Ning, Qiu‐Li; Liang, Hao‐Jie; Yang, Xu; Wang, Jiawei; Liu, Mingkai; Zhang, Jing‐Ping; Wang, Xinlong; Wu, Xing‐Long
Abstract: In order to develop the promising anode material for lithium‐ion batteries with high capacity, high rate performance, and long cycling stability, carbon‐coated FeP nanorods (FeP@C‐NR) vertically grown on the carbon nanotubes (CNTs), defined as CNTs⊥FeP@C‐NR, is successfully prepared via a simple two‐step process. This upgraded structure with slim FeP@C‐NR and dual‐carbon networks can not only buffer the huge volume change of the active materials during electrochemical reaction process to enhance the cycling stability but also accelerate the electrochemical kinetics. It is disclosed that such a unique structure exhibits a pseudocapacitance‐boosted ultrafast electrochemical kinetic and performs an excellent lithium storage performance. It delivers a high reversible capacity of ≈1130 mAh g −1 at a current density of 0.05 A g −1, remarkable cycling stability of 1129 mAh g −1 after 300 cycles at 0.5 A g −1, 1126 mAh g −1 after 300 cycles at 1 A g −1, and 350 mAh g −1 after 3000 cycles at 2 A g −1, and superior rate capability of 345 mAh g −1 at 5 A g −1 . Moreover, a CNTs⊥FeP@C‐NR//LiFePO4 full cell is assembled, which delivers a reversible capacity of 465 mA h g −1 after 60 cycles at 0.5 A g −1 . Abstract : A novel dual‐carbon enhanced CNTs⊥FeP@C‐NR, consisting of carbon‐coated FeP nanorods (NRs) vertically grown on carbon nanotubes (CNTs), is successfully prepared via a simple two‐step method. The unique structure can speed up the reaction kinetic and stabilize the active FeP inside, making the electrode exhibit a high Li‐storage capacity, ultralong cycling stability, and superior rate performance.